Answer:
![(dy)/(dx) = (4(In x)^(3))/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/yfwxph54i0m4o7xmy1cfdvlir9lx8t3sx7.png)
Explanation:
Solving
![y = (In)^(4)](https://img.qammunity.org/2021/formulas/mathematics/college/1ewkaxf4iol4lwsqd107p8g1m6x50em0e5.png)
Using function of function (Chain Rule)
-----(1)
To simplify the function,
Let u = In x
Differentiating u with respect to x
-------- (2)
Substituting u = In x in the given function
![y = (In x)^(4)](https://img.qammunity.org/2021/formulas/mathematics/college/ijtgvq4ytlb8k8wgsapsdlvax6ot1q5w5w.png)
![y = (u)^(4)](https://img.qammunity.org/2021/formulas/mathematics/college/njoofc98j9b560k7b6v7qjmqzlsaysoxid.png)
Differentiating y with respect to u
![(dy)/(du) = 4u^(3)](https://img.qammunity.org/2021/formulas/mathematics/college/gngxmnkiot31oqtebohibdq52ptw8mz7rl.png)
Now that we have
and
, we can solve for
![(dy)/(dx)](https://img.qammunity.org/2021/formulas/mathematics/high-school/uixpzcj18ltl0o4d3t4rqypg7shavk8rb9.png)
![(dy)/(dx) = 4u^(3) * (1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/v41lnu4ypm99fhadc58dkott2lwjio4daz.png)
Substituting u = In x into the equation,
![(dy)/(dx) = 4(In x)^(3) * (1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/5dfayijbuyclnk6abubslwg4sulgeulkup.png)
![(dy)/(dx) = (4(In x)^(3))/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/yfwxph54i0m4o7xmy1cfdvlir9lx8t3sx7.png)